Micromechanical testing of oxidised grain boundaries in Ni alloy 600 - Stratulat, A; Roberts, S; Stratulat, A; Roberts, S (Materials Research Society, 2013)
Micromechanical testing of focused ion beam (FIB) machined cantilevers was used to study oxidised grain boundaries in Ni-alloy 600. The Ni-alloy 600 samples were exposed in simulated PWR primary water at 325°C for 4500h with a hydrogen partial pressure of 30kPa. The FIB was used to machine small cantilever beams at the selected sites in the Ni alloy 600, cut so that the beam contained a selected grain boundary close to the built-in end. The FIB was also used to make a pre-crack, 700 nm deep, on the grain boundary. Cantilevers were loaded at the free end using a nanoindenter. Cantilevers milled in the un-oxidised sample yielded, and did not fracture. The specimens containing oxidised grain boundaries fractured at the boundary after small amounts of plasticity. Load vs. displacement data were used to calculate the fracture toughness of the oxidised grain boundaries. The fracture toughness associated with fracture of grain boundary oxide for these cantilevers was in the range 0.73-1.82MPa (m)1/2, with an average value of 1.3MPa (m)1/2. We believe this to be the first time the fracture toughness of an oxidised grain boundary has been determined.